The Association between Blood Pressure, Cerebral Perfusion and Late Life Depression - BRIGGS, ROBERT (Trinity College Dublin. School of Medicine. CentreFor Medical Gerontology, 2020)
Background: While late life is generally characterised by contentment and happiness, depression in later life confers an independently increased risk of early mortality, cognitive and functional decline and nursing home admission. Understanding the role of potentially modifiable risk factors that underpin LLD is therefore crucial in terms of population health. One such important modifiable process may be structural changes in the frontal lobe cerebral blood due to impaired cerebral blood flow. Hypothesis We hypothesise that: 1. Conditions, such as orthostatic and systemic hypotension, which predispose to cerebral hypoperfusion, increase the risk of depression in later life by causing structural changes in the frontal lobe. 2. Gait disorders, which are related to structural and functional changes in the frontal lobe, are closely associated with depression in later life and could potentially be used to identify those at risk of incident depression. Methods In order to test this hypotheses we will use the Irish Longitudinal Study on Ageing (TILDA) dataset, involving a sample of adults over 8,000 people aged ≥ 50 years at wave 1 with longitudinal follow-up over 8 years and detailed social and biological data which allows us to control for a wide range important covariates and to conduct robust longitudinal analyses. TILDA also incorporates important objective health measures including active stand testing with finometer for orthostatic blood pressure, near-infrared spectroscopy for cerebral perfusion, as well as spatiotemporal gait analysis. Key Findings -Lower BP and symptomatic OH both independently predict incident depressive symptoms in a large cohort of community-dwelling older people -Depressive symptoms in later life are associated with significantly lower frontal lobe perfusion which is BP-dependant -Cerebral WMH burden is higher in depressed older adults but only in those with lower BP or OH -Gait problems, specifically prolonged Timed Up and Go, slower gait speed and shorter step length, independently predict incident depressive symptoms in later life Discussion These results raise the possibility that hypotension may be a modifiable risk factor for depression in later life. Furthermore, cerebral hypoperfusion may be the mechanism by which hypotension increases the risk of depression. Our findings in relation to depression and gait disturbance are important in the context of emerging evidence that physical activity may be beneficial as an adjunct to standard therapy in LLD, but also because physical activity has been shown to improve cerebral perfusion in later life. These findings are novel, and underline the complex inter-relationship between heart health, brain health and physical health/function in later life, with a particular focus on frontal lobe integrity and function. Our intention is that the findings from these studies will inform a multimodal preventative program aimed at reducing the incidence of depression in older people at risk of mental health problems.
APPROVED
Keywords: Depression; Orthostatic Hypotension; Cerebral Perfusion; Gait; Frontal Lobe; White Matter Hyperintensities